#### Answer

$q'=\frac{2-2r}{3\sqrt[3] (2r-r^2)^2}$

#### Work Step by Step

Take the derivative and apply the chain rule:
$q'=1/3(2r-r^2)^{-2/3}\times(2-2r)=\frac{2-2r}{3\sqrt[3] (2r-r^2)^2}$

Published by
Pearson

ISBN 10:
0-32187-896-5

ISBN 13:
978-0-32187-896-0

$q'=\frac{2-2r}{3\sqrt[3] (2r-r^2)^2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.